2001
DOI: 10.1523/jneurosci.21-24-09814.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Expression and Notch-Dependent Regulation of Neural Progenitors in the Adult Rat Spinal Cord

Abstract: Recent studies have demonstrated that neural stem cells and other progenitors are present in the adult CNS. Details of their properties, however, remain poorly understood. Here we examined the properties and control mechanisms of neural progenitors in the adult rat spinal cord at the molecular level. Adult and embryonic progenitors commonly expressed various homeodomain-type (Pax6, Pax7, Nkx2.2, and Prox1) and basic helix-loop-helix (bHLH)-type (Ngn2, Mash1, NeuroD1, and Olig2) transcriptional regulatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
200
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(223 citation statements)
references
References 57 publications
19
200
3
1
Order By: Relevance
“…Next, we characterized the identity of cells expressing Olig2 (see Table 1, which is published as supporting information on the PNAS web site, for cell type identification criteria). In the intact adult CNS, Olig2 is expressed in mature oligodendrocytes and NG2-positive glial precursors (30)(31)(32). Consistent with these data, the majority of NG2-positive (NG2ϩ) cells in the intact cortical GM (Ϸ70%) contained Olig2, but they only accounted for 26% of the Olig2ϩ cell pool (Fig.…”
Section: Identity Of Olig2-immunopositive (Olig2؉) Cells In the Intacsupporting
confidence: 81%
See 1 more Smart Citation
“…Next, we characterized the identity of cells expressing Olig2 (see Table 1, which is published as supporting information on the PNAS web site, for cell type identification criteria). In the intact adult CNS, Olig2 is expressed in mature oligodendrocytes and NG2-positive glial precursors (30)(31)(32). Consistent with these data, the majority of NG2-positive (NG2ϩ) cells in the intact cortical GM (Ϸ70%) contained Olig2, but they only accounted for 26% of the Olig2ϩ cell pool (Fig.…”
Section: Identity Of Olig2-immunopositive (Olig2؉) Cells In the Intacsupporting
confidence: 81%
“…Indeed, here we could show that antagonizing Olig2 function after stab lesion enabled a small, but significant, number of infected cells to generate neuroblasts. Because many antineurogenic factors are released upon acute brain injury (30,(48)(49)(50), the small number of neuroblasts is no surprise. However, these data show as a proof-of-principle that suppression of antineurogenic determinants allows the progression of at least some precursors in the adult lesioned mammalian cortex toward a neurogenic fate.…”
Section: Discussionmentioning
confidence: 99%
“…This situation can be improved after transduction with potent neurogenic transcription factors (8,24), but the response is still rather limited. Obviously the antineurogenic environment present in the adult brain parenchyma (38) contributes to the predominant glial fate in vivo, with Notch (39) and BMP signaling (40) acting as potential candidates for this fate restriction. In addition, our results now suggest that the limited neurogenic response even after overexpression of neurogenic factors may also be due to targeting glial cells with less plasticity than the multipotent subset of reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that many regions of the adult CNS contain neuronal progenitors that have the ability to generate new neurones and glia. [34][35][36] Several adult CNS regions exhibit neurotropic-factor responsiveness, including the spinal cord. 37 Nieder et al 38 surveyed data relating to the pathogenesis of radiation myelopathy and suggested that the administration of cytokines could increase the proliferation of oligodendrocyte progenitors, upregulate the synthesis of myelin constituents and promote myelin regeneration in the adult CNS.…”
Section: Discussionmentioning
confidence: 99%